Oxford international secondary Science grade 6 - Fullick, Ann (Karachi : Oxford university press, 2023)
The Oxford International Secondary Science Student Book 6 (Second Edition) is designed for secondary school students to deepen their understanding of science. It covers a range of topics including biology, chemistry, physics, and the environment. The book features clear explanations, experiments, and activities that foster inquiry and critical thinking. It also includes practice questions, review sections, and vocabulary-building exercises to reinforce key concepts. Aligned with international curricula, the book encourages hands-on learning and helps students develop a strong foundation in scientific knowledge and skills.
Keywords: Science : Textbook